PHENOLOGY, CLIMATE, AND ADAPTATION: HOW DOES DIPTEROCARPS RESPOND TO CLIMATE? - Winarni, Nurul L.; Kurniasari, Dewi R.; Hartiningtias, Diny; Nusalawo, Meyner; Sakuntaladewi, Niken (Association of Indonesian Forestry and Environment Researchers and Technicians, 2016)
Temperature, rainfall and extreme weather have been indicated to affect the phenological patterns and forest productivity by shifting flowering and fruiting seasons and patterns, as well as crop production. Dipterocarpaceae are high value trees for both timber and non-timber forest products. This study aims to determine the response of phenological patterns of flowering and fruiting of Dipterocarps to climate variables. The study was conducted at Way Canguk Research Station of the Bukit Barisan Selatan National Park (BBSNP), Lampung during May-November 2012 by analyzing 14 years (1998-2012) of phenological data of Dipterocarps. The phenology surveys were carried out on monthly basis by estimating the percentage of flowering, fruiting (divided into 0-4 scoring) and the crop production. The results indicated that the phenological patterns of Dipterocarps in the area depicted major and minor patterns without mass-flowering time, different from what have been reported for Kalimantan or North Sumatra. Minor peak flowering season showed regular flowering, particularly during March to July every year. However, there were major flowering seasons in November 2002 (20.2%), September 2006 (21%), and October-November 2011 (20.3%). Average monthly fruit production showed a peak at the end of the dry season. Major flowering season seemed to coincide with the period of major El Nino events in November 2002 and September 2006, while others associated with La Nina. This study suggest that phenology and climate change may have implications in designing strategies for collection of seed materials to support the conservation and plantation programs of the Dipterocarps.